2019
DOI: 10.1093/rheumatology/kez598
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow-up of Behçet’s syndrome patients treated with cyclophosphamide

Abstract: Objectives CYC remains an important treatment option for Behçet’s syndrome (BS) patients with life-threatening manifestations. However, adverse events may occur with CYC and this has led to increased use of biologic agents in other vasculitides. We investigated short and long term adverse events associated with CYC use in BS patients. Methods We conducted a retrospective chart review of all BS patients treated with CYC betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 37 publications
0
10
0
1
Order By: Relevance
“…However, CYC also has some adverse effects, of which reproductive toxicity is an important issue, since it was seen in 30% of patients within 25 years of follow-up. 26 In addition, hemorrhagic cystitis, a less common adverse effect of CYC in the Chinese population, was still seen in one of our patients in the CYC group. In contrast, the adverse reactions of tocilizumab, such as transient mild liver function impairment and thrombocytopenia, were tolerable.…”
Section: Discussionmentioning
confidence: 65%
“…However, CYC also has some adverse effects, of which reproductive toxicity is an important issue, since it was seen in 30% of patients within 25 years of follow-up. 26 In addition, hemorrhagic cystitis, a less common adverse effect of CYC in the Chinese population, was still seen in one of our patients in the CYC group. In contrast, the adverse reactions of tocilizumab, such as transient mild liver function impairment and thrombocytopenia, were tolerable.…”
Section: Discussionmentioning
confidence: 65%
“…Short-term adverse events include gastrointestinal disturbances, hemorrhagic cystitis, alopecia bone marrow suppression, and infections (Brummaier et al, 2013), while the incidence of secondary malignancies and infertility are long-term and rare adverse events (Appel et al, 2009;Mok, 2016). Gurcan et al (2020) recently found that BD patients treated with CYC were associated with a higher incidence of malignancy in a dose-dependent manner through a retrospective cohort study. In the present investigation, we also identified a higher risk of cancer in patients with BD who used CYC.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic glucocorticoids (GCs) and immunosuppressive or cytotoxic agents including thalidomide, azathioprine (AZA), cyclophosphamide (CYC) and cyclosporine (CsA) are usually combined to treat refractory symptoms or multiple organ involvement ( Lopalco et al, 2020 ). Although the symptoms of BD patients have effectively improved, the adverse reactions associated with long-term drug use given its chronic disease course are also of concern ( Gurcan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This observation may be explained by selection (funneling) bias, as azathioprine is used more in mild cases, whereas biologics are preferred in patients with severe disease manifestations [104,105]. Among cISs, cyclophosphamide should be reserved for remission induction in patients with severe arterial disease due to its high teratogenicity and risk for causing malignancy [106]. Hepatotoxicity, cytopenias, and gastro-intestinal intolerance are among the main limitations of cIS use; however, their relative safety for infections is important for long-term management decisions.…”
Section: Safety Issuesmentioning
confidence: 99%